Odpowiedź :
Odpowiedź:
[tex]W(x)=-4x^3(x+1)(x+6)\\\\-4x^3(x+1)(x+6)=0\ \ /:(-4)\\\\x^3(x+1)(x+6)=0\\\\x^3=0\ \ \ \ \vee\ \ \ \ x+1=0\ \ \ \ \vee\ \ \ \ x+6=0\\\\x=0\ \ \ \ \vee\ \ \ \ x=-1\ \ \ \ \ \ \ \ \vee\ \ \ \ x=-6[/tex]
[tex]Z(x)=5(x^3+27)(x^2-9)\\\\5(x^3+27)(x^2-9)=0\ \ /:5\\\\(x^3+27)(x^2-9)=0\\\\x^3+27=0\ \ \ \ \vee\ \ \ \ x^2-9=0\\\\x^3=27\ \ \ \ \ \ \ \ \vee\ \ \ \ x^2=9\\\\x^3=3^3\ \ \ \ \ \ \ \ \vee\ \ \ \ x=\sqrt{9}\ \ \ \ \vee\ \ \ \ x=-\sqrt{9}\\\\x=3\ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x=3\ \ \ \ \ \ \ \ \vee\ \ \ \ x=-3\\\\x=3\ \ \ \ \ \ \vee\ \ \ \ x=-3[/tex]
[tex]Q(x)=(2x+3)(x^2-x-2)\\\\(2x+3)(x^2-x-2)=0\\\\2x+3=0\ \ \ \ \ \ \ \ \vee\ \ \ \ x^2-x-2=0\\\\2x=-3\ \ /:2\ \ \ \ \vee\ \ \ \ x^2+x-2x-2=0\\\\x=-\frac{3}{2}\ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x(x+1)-2(x+1)=0\\\\x=-\frac{3}{2}\ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ (x+1)(x-2)=0\\\\x=-\frac{3}{2}\ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x+1=0\ \ \ \ \vee\ \ \ \ x-2=0\\\\x=-\frac{3}{2}\ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x=-1\ \ \ \ \ \ \vee\ \ \ \ x=2[/tex]